Metode Guru Dalam Dalam Mengajarkan Tata Cara Shalat Pada Anak Down Syndrome di Sekolah Dasar Alam Mahira Kota Bengkulu - Annisa Ul Aputri; Fidhia Andani; Erna Meisarwati; Inanda ika; Nisa Nurjanah (JPT : Jurnal Pendidikan Tematik, 2023)
This study aims to determine the teacher's method in teaching prayer procedures to 6th grade Down syndrome children at Almahira Elementary School in Bengkulu City. This type of research is qualitative research, namely research that attempts to provide a systematic format of actual facts and characteristics of a particular population. The collection of research data uses observation, interview, and documentation methods. Furthermore, the data is analyzed using data triangulation, namely by combining several data collection techniques such as interviews, observations, and data sources in the form of library materials, informants, teaching and learning activities, and documentation. The results of the study indicate that teachers have a very important method in the process of teaching prayer procedures. Here, teachers must be able to understand and comprehend the conditions of their students, especially in teaching children who have physical, mental, or other disabilities. Teachers must also provide space for their students by providing feedback in the form of questions and answers on problems that are not yet known by students with the aim of developing their potential, in addition, teachers must also know and have their own methods in teaching prayer procedures so that they can overcome problems and obstacles faced when the process of teaching prayer begins to be ineffective. Teachers also need to evaluate themselves in delivering material to find out where their weaknesses lie in delivering the material.